2008
DOI: 10.1111/j.1432-2277.2008.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors forEnterobacteriaceaebacteremia after liver transplantation

Abstract: Summary Enterobacteriaceae are now the predominant pathogens isolated in bloodstream infections complicating orthotopic liver transplantation (OLT). We conducted a retrospective cohort study of patients who underwent OLT in a University hospital between 01/01/1997 and 31/03/2003 to investigate the risk factors of Enterobacteriaceae bacteremia (EB) after OLT. EB was defined as the isolation of an Enterobacteriaceae species from at least one blood culture within 3 months following OLT. Pre‐, per‐ and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 27 publications
4
41
1
3
Order By: Relevance
“…(25) In a univariate analysis, Hsieh et al (7) demonstrated that a high MELD score is a risk factor for A. baumannii infection after LT.…”
Section: Discussionmentioning
confidence: 99%
“…(25) In a univariate analysis, Hsieh et al (7) demonstrated that a high MELD score is a risk factor for A. baumannii infection after LT.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent septic graft loss high-risk patients with HPS should be transplanted with a low MELD score. 12 Although our patient had severe hypoxemia and a high shunt fraction, she had a low MELD score of 15 and no primary cardiopulmonary disease. Thus, she had "pure" HPS, which suggests that "pure" HPS with a low MELD score should respond well to LT, even if the hypoxemia is severe.…”
Section: Discussionmentioning
confidence: 97%
“…3; Table 2). This suggests that the contact of the fly with food might be enough to produce contamination that causes an infection (Manrique & Delfín 1997), and may be associated with bacteremia, septicemia, intestinal infections and nosocomial diseases (Bellier et al 2008).…”
Section: Discussionmentioning
confidence: 99%